Application of recycled concrete aggregates in continuous-graded cement stabilized macadam - Xinglong Xiang; Wenlin Chen; Yifan Huang; Peng Wang; Guan Wang; Jinliang Wu; Wenyu Tian (Case Studies in Construction Materials)
This study investigates the potential of using recycled concrete aggregate (RCA) derived from construction and demolition waste as a replacement for natural aggregate in cement-stabilized macadam (CSM). Various substitution rates of RCA, ranging from 0 % to 100 %, were examined with a focus on mechanical properties and durability, including unconfined compressive strength (UCS), indirect tensile strength (ITS), compressive elastic modulus, drying shrinkage, frost resistance, scour resistance, and water damage resistance. Nanoindentation was used to analyze the interfacial transition zones (ITZs) within the CSM. The results show that with a fixed cement content, the UCS, ITS, and compressive elastic modulus decrease as the RCA content increases. Higher RCA content also leads to reduced drying shrinkage, frost resistance, scour resistance, and water damage resistance. Nanoindentation revealed that ITZ1 and ITZ2 have similar thicknesses (∼50 μm), while ITZ3 is about 80 μm thick, highlighting the intricate physical composition of ITZs, including pores, low-density C-S-H, high-density C-S-H, and Ca(OH)2. These findings provide critical insights for optimizing sustainable CSM design using RCA, thereby promoting environmental sustainability in road construction.